Strengthening human and physical resources towards a functional and innovative halal goat science center - Yasin, Noraisa K. (Journal of Halal Product and Research (JHPR), 2025)
The Halal Goat Science and Innovation Center (HGSIC) was established at Sultan Kudarat State University (SKSU) under Project 4 to address the complex challenges of ensuring halal integrity in goat production. Funded by the Department of Science and Technology (DOST), the project developed TESDA-accredited competency courses in halal goat husbandry, slaughtering, and processing, alongside essential manuals on Good Manufacturing Practices (CGMP) and Sanitation Standard Operating Procedures (SSOP). The Center features a comprehensive infrastructure, including training facilities, a halal-dedicated prayer room, and a Double-A accredited slaughterhouse certified by the National Meat Inspection Service (NMIS) for compliance with rigorous food safety standards. SKSU trained 25 staff members in halal goat science disciplines to enhance its expertise, with 10 achieving NCII competency and one PhD-trained halal expert spearheading initiatives. While TESDA accreditation as a training and testing facility remains pending, the institutionalization of HGSIC was formalized through SKSU's Board of Regents Resolution No. 117-2023, ensuring its sustainability. These achievements solidify the Center’s role as a leading hub for halal goat science, entrepreneurship, and collaborative research, setting a benchmark for halal compliance and innovation in the industry. Keywords: Halal Goat Science and Innovation Center (HGSIC); Department of Science and Technology (DOST); Good Manufacturing Practices (CGMP); Sanitation Standard Operating Procedures (SSOP); National Meat Inspection Service (NMIS)